Enhancing resource efficiency and value addition in food and agricultural by-product processing: a green recycling approach - Fu, Pei; Zhang, Yi (Frontiers in Sustainable Food Systems, 2025)
This study presents an innovative green recycling model designed to enhance resource efficiency and value addition in the processing of food and agricultural by-products. The model integrates a resource circulation system to streamline by-product flow across the industrial chain. It optimizes resource allocation and logistics using advanced algorithms and network analysis. We developed an eco-friendly processing technique with modern green technologies. This approach enhances by-product conversion rates while reducing energy consumption. Real-time data collection and intelligent monitoring ensure efficient operation and maximize resource utilization. Experimental results show high effectiveness, with utilization rates of rice bran, wheat bran, and rice husk at 85.4, 82.7, and 88.1% in the processing phase, rising to 92.3, 90.4, and 93.2% in the transformation phase. These rates reflect a substantial improvement in both initial utilization and recycling efficiency. Additionally, the contributions of physical, chemical, and biological treatment methods to the overall value addition of the industrial chain were 35, 27, and 22% respectively, highlighting the synergistic effects of these technologies in enhancing resource value. This research offers a robust theoretical foundation and practical guidance for the green recycling of food and agricultural by-products, promoting sustainable development and resource efficiency in the industry.